Polybius and His Legacy - Miltsios, Nikos (Trends in Classics - Supplementary Volumes Ser, 2018)
Intro -- Preface -- Contents -- Introduction -- Part I: Key Themes and Ideas -- Polybius and Ethnicity -- Polybian Barbarology,Flute-Playing in Arcadia, and Fisticuffs at Rome -- Polybius and the Tyrants of Syracuse -- Past and Present as paradoxon theōrēma in Polybius -- Praise in Polybius -- Being, Seeming and Performing in Polybius -- Part II: Narrative and Structure -- A Survey on the Speeches in Polybius -- Documents and Narrative: Reading the Roman-Carthaginian Treaties in Polybius' Histories -- Incomplete and Disconnected: Polybius, Digression, and its Historiographical Afterlife -- The Historian's Craft: Narrative Strategies and Historical Method in Polybius and Livy -- Part III: Intertextual Relationships -- Polybius and Xenophon: Hannibal and Cyrus the Great as Model Leaders -- The Εncomium of Philopoemen and its Ιsocratic Βackground -- Polybius and Biography -- Polybius and the Legacy of Fourth-Century Historiography -- Polybius and Fifth-Century Historiography: Continuity and Diversity in the Presentation of Historical Deeds -- Part IV: Reception -- Polybius and Arrian: The Cases of Philip V and Alexander the Great -- Appian, the Third Punic War and Polybius -- Lost in Reception? Polybius' Paradoxical Impact on Writing History in Republican Rome -- Odysseus, Rome, and the First Punic War in Polybius' Histories -- Silius Italicus and Polybius: Quellenforschung and Silian Poetics -- Polybius and Oscar Wilde: Pragmatike Historia in Nineteenth Century Oxford -- List of Contributors -- General Index.